(untitled) (mathematica didactica, 2006)
Student teachers often express the wish to integrate applications in their future mathematics lessons. But do their beliefs about the usefulness of mathematics support this wish or can they be regarded as an obstacle? The paper presents a theoretical concept to analyse the beliefs about the usefulness of mathematics. Following this, remarks of the student teachers will be analysed and categorised. The reconstructed beliefs indicate that it may not be easy to reach the goals linked with the integration of applications in mathematical lessons.